Some Theoretical and Practical Issues of Implementation of the Functions Arising from the Constitutional Status of the RA Court of Cassation - Ghazinyan, Gagik (Bulletin of Yerevan University C: Jurisprudence, 2022)
In the article, the author has analyzed some institutional issues of the formation of the country’s highest court in the light of the analysis of the constitutional status of the Court of Cassation. In particular, in the context of ensuring the external independence of the judiciary, the procedure for the selection of the president and judges of the Court of Cassation by the RA National Assembly has become the subject of legal criticism. Taking into account the most important constitutional mission of the country’s highest court to ensure the uniform application of the law, the mitigation of the requirements for the candidate of the judge of the Court of Cassation as a result of the recent legislative changes was assessed as illegitimate. With the same observation, the formation of the anti-corruption chamber in the RA Court of Cassation was assessed as problematic.
Keywords: uniform application of the law; independence of the judiciary; procedure for selection (appointment) of judges; legislative power; specialization of judges (courts); requirements for judges; anti-corruption chamber